2015
DOI: 10.1002/ece3.1727
|View full text |Cite
|
Sign up to set email alerts
|

Snow vole (Chionomys nivalisMartins) affects the redistribution of soil organic matter and hormone‐like activity in the alpine ecosystem: ecological implications

Abstract: In alpine environments, colonies of snow vole (Chionomys nivalis Martins) cause strong pedoturbation, which may affect humification process and soil organic matter (SOM) cycling, with repercussions on the hormone‐like activity of organics. We investigated the effect of snow vole pedoturbation on the chemical and spectroscopic features of soil organic fractions, and the potential hormone‐like activity of humic and fulvic acids (HA, FA). The study site was located on the high‐mountain environment of the Majella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The separation of the three sandy-textured soils and the G, R, and AFS management systems from the Organosol under monoculture (M) management confirms that the mineral fraction directly affects the structural and compositional quality of HA (horizontal grouping in Figure 6). The effects of HS on soil fertility and characteristics have been extensively reported in the literature (Kögel-Knabner, de Leeuw, & Hatcher, 1992;Mamedov et al, 2016;Piccolo, Conte, & Cozzolino, 1999;Pizzeghello et al, 2015;Senesi & Plaza, 2007;Tan, 2014). However, this study distinguishes the types of HA structures with the strongest relationships with the chemical or physical attributes ( Figure 6).…”
Section: Relationship Between Ha Structure and Composition And Soilmentioning
confidence: 89%
“…The separation of the three sandy-textured soils and the G, R, and AFS management systems from the Organosol under monoculture (M) management confirms that the mineral fraction directly affects the structural and compositional quality of HA (horizontal grouping in Figure 6). The effects of HS on soil fertility and characteristics have been extensively reported in the literature (Kögel-Knabner, de Leeuw, & Hatcher, 1992;Mamedov et al, 2016;Piccolo, Conte, & Cozzolino, 1999;Pizzeghello et al, 2015;Senesi & Plaza, 2007;Tan, 2014). However, this study distinguishes the types of HA structures with the strongest relationships with the chemical or physical attributes ( Figure 6).…”
Section: Relationship Between Ha Structure and Composition And Soilmentioning
confidence: 89%
“…In fact, both HA and FA of all the soils showed a hormone-like activity that might contribute to regulate the growth of the root main axes and their density, and the surface absorbing area. In this way, the plants would be able to uptake a higher amount of nutrients because of the stimulation offered by the humic substances formed in the soil [21,22]. The HA extracted from the soil derived from serpentinite displayed the greatest auxin-like activity.…”
Section: Hormone-like Activity Of Ha and Famentioning
confidence: 99%
“…Among the strategies adopted, symbiosis with arbuscular mycorrhizal fungi allow vegetation to increment its edaphic tolerance (e.g., [19]). Among the soil-plant relationships that are functional in terms of improving plant resilience and, consequently, biomass production and soil carbon sequestration, the hormone-like activity of the humic substances seems to have an important role [20][21][22]. Humic substances exert a hormone-like activity due to the presence of indole-3-acetic acid (IAA), a plant hormone of the auxin class [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted in alpine environments found that colonies of snow vole ( Chionomys nivalis Martins) caused a strong modification of the organic matter turnover, which determined the prevalence of the humification process. The HS arising from this soil organic matter cycling exhibited a high auxin‐like activity ( Pizzeghello et al, 2015).…”
Section: The Hs Auxin Effectmentioning
confidence: 99%